2022
DOI: 10.1002/glr2.12019
|View full text |Cite
|
Sign up to set email alerts
|

Climate and anthropogenic drivers of changes in abundance of C4 annuals and perennials in grasslands on the Mongolian Plateau

Abstract: Background C4 plants have increased substantially during the past several decades in the grasslands of the Mongolian Plateau due to regional warming. Here, we explore how the patterns of abundances of C4 annuals and C4 perennials change over space and time. Methods A total of 280 sites with C4 plants were surveyed in four types of grasslands in 9 years. The relative biomasses of C4 plants (PC4), C4 annuals (PA4), and C4 perennials (PP4) were calculated. Structural equation modeling was used to analyze the driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…They found that increasing grazing intensity favoured stoloniferous plants, rosette formation likeliness, short height, and increased the abundance of short-lived and fast-growing species when climatic conditions and grazing history were both taken into consideration. Some findings of the above meta-analysis were partly confirmed for sheep-grazed pastures by Pettit et al (1995), Yang et al (2022) and Farmilo et al (2023). However, none of the above papers studied the biomass of life-and growth form groups along a gradient of grazing intensity in sheep grazed pastures.…”
Section: Introductionmentioning
confidence: 62%
“…They found that increasing grazing intensity favoured stoloniferous plants, rosette formation likeliness, short height, and increased the abundance of short-lived and fast-growing species when climatic conditions and grazing history were both taken into consideration. Some findings of the above meta-analysis were partly confirmed for sheep-grazed pastures by Pettit et al (1995), Yang et al (2022) and Farmilo et al (2023). However, none of the above papers studied the biomass of life-and growth form groups along a gradient of grazing intensity in sheep grazed pastures.…”
Section: Introductionmentioning
confidence: 62%
“…These results indicate a reduced role for species interactions over plant communities in patchy degraded grasslands. An increase in abundance of annual plants is typical of grassland degradation (Chen et al, 2017) and contributes to the low stability of grassland ecosystems (Yang et al, 2022). The high abundance of annual plants induced by PD observed here is a further indication of the instability of patchy degraded grassland ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Third, plant roots in different soil layers often perform different functions with respect to water acquisition. Shallow roots typically absorb rainwater, while deep roots can absorb groundwater (Yang et al., 2022), and grassland plants can adjust the vertical distribution of their roots along a soil profile to adapt to drought or wet conditions (Zhang et al., 2019). Finally, soil microbes such as bacteria and fungi usually obtain carbon from plant roots and help plants acquire soil nutrients (Chen et al., 2015).…”
Section: Introductionmentioning
confidence: 99%